Evaluation of performances of Limousin sire candidates in the performance test station - Tőzsér, János; Szűcs, Márton (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
Performance test results of Limousin (n=40) pure bred sire candidates obtained between 2018 ands 2020 were analized. Sire candidates were kept in small goup (2-9) in pen at the Performance Test Station and feeding based on ad libitum grass hay, or alfa-alfa hay and rationed bull’s feed. Analyzed characteristics were as follows: body weight at the start and at the finish of the test, daily weight gain during self performance test (g/ day), daily weight gain during life, (g/day), four body measurements (ex. withers’ height, pin with, cm), 16 results of linear scoring (ex: top line, rump angle, legs, score), and genomic scores (GS) for 8 traits (ex: easy calving, vigor of growth, musculatity, score). Data were processed using SPSS 18. program package (cluster analysis, independent samples T-test, Mann-Whitney U-Test). Cluster 5 (height at withers) appeared separately from the other parameters, confirming the professional importance of this feature in practice. Regarding genomic scores, it is noteworthy that the score for muscularity (cluster 3) was different from clusters 1, 5, 2, 4, 6, 8, 7, which were placed in a group. The breeding bull candidates with a high final body weight (≥600 kg) have good characteristics, their general appearance is more favorable, measurements are wider and taller, and their round of rump is also more favorable than that of their contemporaries.